MASIHKAH JOB SATISFACTION DAN MOTIVATION MEMENGARUHI ORGANIZATIONAL COMMITMENT? - Retno Sari Murtiningsih; Tiara Puspa (Lembaga Penerbit Fakultas Ekonomi dan Bisnis, 2019)
This research is concerning the influence of job motivation and job satisfaction on organizational commitment. The purpose of this study is to see how far the influence of job motivation and job satisfaction on organizational commitment. This study uses primary data obtained from 150 respondents. The sample was selected by using purposive sampling technique. The dependent variable in this study is organizational commitment, while the independent variables are job motivation and job satisfaction. This study used the structural equation modeling (SEM) to test job motivation, job satisfaction and organizational relationship models. The results show that job motivation positively influences job satisfaction, but job satisfaction surprisingly does not have positive and significant effect on organizational commitment. Furthermore, job motivation positively influence organizational commitment